Rerum Novarum: Theological Reasoning for the Public Sphere? - Daughton, Amy (Studies in Christian ethics, 2019)
Contemporary Catholic Social Teaching has increasingly come to bear on the moral and political horizons of our interdependent lives, seeking to address the nature and purpose of our common striving for human flourishing. Frequently, Rerum Novarum is identified as an origin point for CST as a distinctive thread within the deeper tradition of Catholic theology attentive to justice and the common good. The focus on justice in labour practices, especially living wages and social participation, demonstrates its contemporary relevance, but can it contribute to the public debate on such issues, beyond the framework of its particular convictions? This article suggests that Rerum Novarum offers theological reasoning in and for the public sphere by way of its insistence on the social bond as foundation and task; the role of political and cultural plurality in formation and action; and a rich vision of public life as morally participatory for all.